Green and simple approach for low-cost bioproducts preparation and CO2 capture. (September 2021) - Durán-Jiménez, Gabriela; Kostas, Emily T.; Stevens, Lee A.; Meredith, Will; Erans, Maria; Hernández-Montoya, Virginia; Buttress, Adam; Uguna, Clement N.; Binner, Eleanor
Abstract: This study has demonstrated, for the first time, a simple, fast and flexible microwave processing method for the simultaneous preparation of bio-products (bio-oil, bio-gas and biochar) using a methodology that avoids any form of catalyst or chemical activation. The dielectric properties of biomass and physicochemical characterisation such as TGA, elemental and proximate analysis, XRD, SEM/EDX and textural properties, showed that 8 kJ g −1 of microwave energy can produce superior biochars for applications in CO2 capture. The maximum CO2 uptake capacity for biochar produced was 2.5 mmol g −1 and 2.0 mmol g −1 at 0 and 25 °C and 1 bar, which and also exhibited high gas selectivity compared with N2, fast kinetics of adsorption (<10 min) and desirable reusability (>95%) after 20 cycles. GC-MS analysis of generated bio-oil products revealed that higher microwave energies (>8 kJ g −1 ) significantly enhanced the amount of bio-oil produced (39%) and specifically the formation of levoglucosan, furfural and phenolics compounds, and bio-gas analysis identified trace levels of H2 and CH4 . The results from this study confirm a green, inexpensive and efficient approach for biomass valorisation which can easily be embedded within bio-refinery process, and also demonstrates the potential of biochars for post-combustion CO2 uptake. Graphical abstract: Image 1 Highlights: Microwave pyrolysis by simple approach was investigated. Microwave energy influenced bio-oil yields and bio-char textural properties. Bio-oils contained high abundance of phenolic compounds. CO2 uptake (2.5 mmol g −1 ) was achieved by biochar prepared at 400 W and 6 min. Bio-char CO2 kinetics, selectivity and reusability was investigated.